Staged entrepreneurship: the formation of hybrid and spawning entrepreneurial intentions - Leif Brändle; Andreas Kuckertz (Journal of Business Economics, 2021)
Most individuals find their way into entrepreneurship through combinations of self-employment and paid employment. However, prior research on entrepreneurial intentions has overlooked intended career transitions. Drawing on social cognitive career theory, we argue that, against the background of personal and environmental factors, individuals form career intentions that involve the combination of and transition between paid employment and self-employment. Such staged entrepreneurial intentions include the delay of entrepreneurial entry by intermediate stages of paid employment (i.e., spawning entrepreneurial intentions) or immediate entrepreneurial entry in parallel combination with paid employment at established organizations (i.e., hybrid entrepreneurial intentions). We test these theoretical ideas based on a survey involving 1003 individuals prior to career entry. The results indicate that individuals proactively align their envisioned career stages according to expected socio-cognitive enablers and barriers (i.e., their entrepreneurial self-efficacy, personal attitudes to entrepreneurship, subjective norms, and socioeconomic status). Notably, we find that individuals with lower levels of perceived social support for an entrepreneurial career more likely intend to combine their existing entrepreneurial activities with a conventional career at an established organization. Furthermore, individuals from lower socioeconomic status backgrounds as well as women are more likely to delay entrepreneurial entry by starting their professional careers in paid employment. The study's primary contribution is the introduction of a novel perspective on entrepreneurial intentions based on individuals' intended career transitions.
Keywords: M13; D91; L26; M5; 650; Entrepreneurial intention; Entrepreneurial careers; Hybrid entrepreneurship; Spawning entrepreneurship; Social cognitive career theory